Efficient oxygen reduction electrocatalyst from graphene by simultaneously generating pores and nitrogen doped active sites - Palaniselvam, Thangavelu; Aiyappa, Harshitha Barike; Kurungot, Sreekumar (Journal of Materials Chemistry, 2012)
A simple way to simultaneously create pores and nitrogen doped active sites on graphene for the electrochemical oxygen reduction reaction (ORR) is developed. The key aspect of the process is the in-situ generation of Fe2O3 nanoparticles and their concomitant dispersion on graphene by pyrolyzing graphene oxide (GO) with the iron phenanthroline complex. Thus the deposited Fe2O3 nanoparticles act as the seeds for pore generation by etching the carbon layer along the graphene-Fe2O3 interface. Detection of the presence of Fe3C along with Fe2O3 confirms carbon spill-over from graphene as a plausible step involved in the pore engraving process. Since the process offers a good control on the size and dispersion of the Fe2O3 nanoparticles, the pore size and distribution also could be managed very effectively in this process. As the phenanthroline complex decomposes and gives Fe2O3 nanoparticles and subsequently the pores on graphene, the unsaturated carbons along the pore openings simultaneously capture nitrogen of the phenanthroline complex and provide very efficient active sites for ORR under alkaline conditions. The degree of nitrogen doping and hence the ORR activity could be further improved by subjecting the porous material for a second round of nitrogen doping using iron-free phenanthroline. This porous graphene enriched with the N-doped active sites effectively reduces oxygen molecule through a 3e(-) pathway, suggesting a preferential shift towards the more favourable 4e(-) route compared to the 2e(-) reaction as reported for many N-doped carbon nano-morphologies. The 90 mV onset potential difference for oxygen reduction as compared to the state-of-the art 20 wt% Pt/C catalyst is significantly low compared to the overpotentials in the range of 120-200 mV reported in the literature for few N-doped graphenes.